(3QSGdI aj GdScfLHjfs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3bGd eMeO Hf RcQjG GdQGRj(B: (3SGdJ jGCHG SYjO, CSYOc Gddg aj LejY CehQc , Cf CQSe Led efGaY GdTQGH GdeSej ScfLHjf s
(3BNQgG (B:s
(3hef CSQa aj ESJYeGdg Ke de jcf bhi GdcHO hGdeYOI BPGg cKjQkG hdhGgH GdYbd GdMeO ddg HdG EfJgGA s
(3Vef eLehY , JQJjHgG (B: (3ef U (B125 - (3U(B128s
(3GdeYQhas
(3Cf QSGdI GdScfLHjf gPg ddTjN EHf SjfGs
(3hUa ajgG dCHj SYjO Hf CHj GdNjQ efGaY TQGH GdScfLHjf (B- (3GfXQ agQS GdWH HQbe (B128 (3dcf SRLjf jLYdgG Vef eDdaGJ GdQGRj QGLY(BGAS III 288s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdWHs